Rising congenital syphilis rates in Canada, 1993–2022 - Tetteh, Ashorkor; Abdi, Nadifa; Moore, Victoria; Gravel, Geneviève (Frontiers in Public Health, 2025)
IntroductionThe number of cases of confirmed early congenital syphilis has risen steeply in Canada in recent years, particularly since 2018, to the highest number ever recorded since national reporting began in 1993. We analyzed national data on confirmed early congenital syphilis from 1993 to 2022 to describe epidemiologic trends in Canada during this period.MethodsData from 1993 to 2017 were obtained from routine surveillance conducted through the Canadian Notifiable Disease Surveillance System, and data from 2018 to 2022 were obtained from enhanced surveillance conducted through a federal-provincial-territorial working group. Case counts and rates were computed nationally and by province and territory. Infectious syphilis data from the same time period for females of reproductive age were also analyzed.ResultsThe national rate of confirmed early congenital syphilis was 127-fold higher in 2022 than in 1993, increasing from 0.3 to 32.7 cases per 100,000 live births. Case counts began increasing rapidly in 2018, with the highest case count observed to date (n = 115) occurring in 2022. The highest rates in the country in recent years have been observed in Saskatchewan, Manitoba, Alberta, and Ontario. Infectious syphilis rates among females of reproductive age have also been rapidly increasing in these provinces. Between 2018 and 2022, the national rate of confirmed early congenital syphilis increased approximately seven-fold and the national rate of infectious syphilis increased approximately two-fold, including an approximately three-and-a-half-fold rate increase among females of reproductive age.DiscussionThese numbers represent huge shifts in the epidemiological landscape of syphilis in Canada. The increase in vertical transmission appears to be driven by not only the increasing rate of infectious syphilis among females of reproductive age but also by multiple structural and social determinants of health impacting pregnant individuals.